Natriuretic Hormones, Endogenous Ouabain, and Related Sodium Transport Inhibitors - Hamlyn, John M. (Frontiers in Endocrinology, 2014)
The work of deWardener and colleagues stimulated longstanding interest in natriuretic hormones (NH). In addition to the atrial peptides (APs), the circulation contains unidentified physiologically-relevant NHs. One NH is controlled by the central nervous system (CNS) and likely secreted by the pituitary. Its circulating activity is modulated by salt intake and the prevailing sodium concentration of the blood and intracerebroventricular fluid, and contributes to postprandial and dehydration natriuresis. The other NH, mobilized by atrial stretch, promotes natriuresis by increasing the production of intrarenal dopamine and/or nitric oxide. Both NHs have short (<35 minutes) circulating half lives, depress renotubular sodium transport, and neither requires the renal nerves. The search for NHs led to endogenous cardiotonic steroids (CTS) including ouabain-, digoxin-, and bufadienolide-like materials. These CTS, given acutely in high nanomole to micromole amounts into the general or renal circulations, inhibit sodium pumps and are natriuretic. Among these CTS, only bufalin is cleared sufficiently rapidly to qualify for an NH-like role. Ouabain-like CTS are cleared slowly, and when given chronically in low daily nanomole amounts, promote sodium retention, augment arterial myogenic tone, reduce renal blood flow and glomerular filtration, suppress nitric oxide in the renal vasa recta, and increase sympathetic nerve activity and blood pressure. Moreover, lowering total body sodium raises circulating endogenous ouabain. Thus, ouabain-like CTS have physiological actions that, like aldosterone, support renal sodium retention and blood pressure. In conclusion, the mammalian circulation contains two non-AP NHs. Identification of the CNS NH should be a priority.